Research and Development in Intelligent Systems XXX Incorporating Applications and Innovations in Intelligent Systems XXI Proceedings of AI-2013, The Thirty-third SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence - Bramer, Max; Petridis, Miltos (Springer International Publishing : Imprint: Springer, 2013)
The papers in this volume are the refereed papers presented at AI-2013, the Thirty-third SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2013 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Knowledge Discovery and Data Mining I, Knowledge Discovery and Data Mining II, Intelligent Agents, Representation and Reasoning, and Machine Learning and Constraint Programming, followed by application stream sections on Medical Applications, Applications in Education and Information Science, and AI Applications. The volume also includes the text of short papers presented as posters at the conference. This is the thirtieth volume in the Research and Development in Intelligent Systems series, which also incorporates the twenty-first volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field.